Quality Culture-Oriented Leadership Model Head of Islamic State Senior High School in Palu - Taufik, (International Journal of Scientific Research and Management (IJSRM), 2021)
Three schools implementing a quality culture-oriented leadership model are MAN 1, MAN 2, and MAN Insan Cendekia in Palu. This research aims to find and explain the development of culturally oriented leadership models in improving education quality in Islamic schools in Palu. This research has been conducted through interview techniques, documentation, and observations in which data results are studied and analyzed based on leadership theory. The result of this research finding is that the successful application of quality culture-oriented leadership occurs because the head of Islamic schools can develop three models of leadership in their schools: (1) transactional leadership model oriented to the ability of the head of Islamic school in meeting the needs of teachers, education staff, and students to improve the progress and quality of Islamic school education; (2) transformative leadership model that provides the understanding of the head of Islamic school on the school’s need and appreciation for the efforts made by education implementers to advance the education in Islamic school; (3) Visionary leadership model that can make Islamic school can realize the achievements of their vision well in the process of organizing education. Through these three models, quality-oriented leadership was developed in MAN 1, MAN 2, and MAN Insan Cendikia in Palu.